Environmental protection of foreign firms in Germany: Does the country of origin matter? - John P. Weche Gelübcke; Isabella Wedl (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
Only recently have the aspects of pollution and environmental protection entered into the empirical literature about international firm activities. The present paper is the first firmlevel study on the link between foreign ownership and environmental protection in Germany. We find that, ceteris paribus, foreign owned firms in Germany are more likely to invest in environmental protection. They also invest on a larger scale in terms of add-on measures as well as integrated measures. These results are robust against different measures, different time periods, different control groups, and selection issues arising from fractional response data. Once we control for productivity levels, the differences become less straightforward. However, the higher probability of foreign firms' making general as well as integrated environmental protection investments and the tilt of their composition towards integrated measures remain. We cannot find any support for differences among foreign firms by country of origin. This can be interpreted as support for the new institutionalist hypothesis of international convergence of management practices in the field of environmental management due to normative pressure and de facto standards at the global level.
Keywords: F21; Q52; Q55; Q56; 330; environmental protection; foreign ownership; country of origin; multinational enterprises; manufacturing; Germany